18F-FDG PET/computed tomography may predict the outcome of newly diagnosed indolent non-Hodgkin lymphoma in patients managed with initial 'watch-and-wait' approach. Issue 12 (December 2020) - Luo, Yaping; Zhang, Ying; Pan, Qingqing; Zhang, Yan; Li, Fang
Abstract : Objective: The aim of this study was to investigate the role of 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) in the outcome of non-Hodgkin lymphoma (NHL) in patients managed with initial 'watch-and-wait' treatment. Methods: Sixteen patients with newly diagnosed NHL treated with initial watchful waiting were retrospectively recruited. They had a baseline 18 F-FDG PET/CT and at least one follow-up PET/CT. The standard uptake values (SUV), metabolic tumor volume (MTV) and total lesions glycolysis (TLG) of lymphoma were measured in PET/CT. They were followed up for at least 2 years or until disease progression. The endpoint was the time to initiation of lymphoma treatment (TLT). Results: Comparing the baseline and the follow-up PET/CT, four out of 16 patients showed spontaneous regression of lymphoma, three of the 16 patients had stable disease and the remaining nine of the 16 patients had progressive disease in the follow-up PET/CT. After a median follow-up of 32 months (range 14–90 months), 10/16 patients had progressive disease and chemotherapy was initiated. The median TLT was 21.0 months. In univariate analysis, MTV and TLG in baseline PET/CT were significant to predict TLT. Kaplan–Meier curves showed a statistical difference for TLT in the two groups of patients stratified by MTV or TLG at baseline (median TLT, 66.0 months vs. 12.0 months, P = 0.007). However, patients' age, Ann Arbor staging, International Prognostic Index and SUVmax were not significant. Conclusion: A proportion of patients with NHL might experience spontaneous regression of lymphoma. 18 F-FDG PET/CT turned out as a prognostic factor for TLT in patients with NHL under watchful waiting.